Student Pharmacists' Perspectives of In-Person versus Virtual Research Poster Presentations - David R. Axon; Megan Whaley (MDPI AG, 2022)
This study assessed the preferences of fourth-year student pharmacists for an in-person versus virtual pharmacy research poster session. An electronic survey was administered to all fourth-year student pharmacists enrolled in a research project course in Fall 2021 (n = 132). Six items explored students' opinions towards research posters using a five-point agreement scale. Twelve items explored students' preferences for either research poster format. Students also indicated their overall preference for an in-person or virtual research poster session. Data were analyzed descriptively. A total of 63 fourth-year student pharmacists completed the questionnaire. The median agreement score was four out of five, indicating favorable attitudes towards the importance of research posters in pharmacy curriculum. Most students said they would enjoy research posters more, and would be more able to present at, participate in and ensure that all can participate in poster sessions if the poster sessions were virtual as opposed to in-person. Most (76.2%) students indicated a preference for virtual rather than in-person research poster sessions. In conclusion, the study results suggest that student pharmacists prefer virtual rather than in-person poster sessions. Further research is recommended to explore the comparative effectiveness of these poster formats to achieve learning outcomes in varying university pharmacy programs.